DESAIN PRIMER GEN EDNRB EKSON 1 UNTUK ANALISIS MUTASI GEN PADA HIRSCHSPRUNG’S DISEASE - Wahyuni, Nur Anisa; Yuni Ahda (Department of Biology, Faculty of Mathematics and Natural Sciences, Hasanuddin University, 2025)
The endothelin receptor type B (EDNRB) gene is located on chromosome 13, consisting of 7 exons and 6 introns. The EDNRB protein produced from this gene belongs to the family of G-protein coupled receptors. Mutations in the EDNRB gene play a role in some cases of Hirschsprung's cause, although the frequency is low. This study aims to design primers and test specificity using BLAST primers to determine the specific primer attached to the EDNRB gene. Primers were designed using Geneious Prime, which were then analyzed in silico based on good primer criteria. The results of this research showed that primers made using Geneious Prime produced the best primers, namely forward primer 5'-GAGTTCGGAGCTTTGCCT-3' and reverse 5'-AGCCCACCA TGATTTCA GC-3' and the results of the specificity test showed that the primer specifically attached to chromosome 13 which is the location of the EDNRB gene (13q22) with a product length of 879 bp. Kata kunci : EDNRB Gene, Primer Design, Hirschsprung’s Disease